The Effect of Online Advertising of Football Players on Fans' Purchase Intention with the Mediating Role of Players' Popularity - Fereshteh Aghajani; Vajiheh Javani (Sports Business Journal)
Purpose: Online advertising has become a crucial tool for sports teams, marketers, and retailers looking to engage with fans and boost sales of sports-related products. This study examines the effect of online advertising of football players on fans' purchase intention, with the mediating role of players' popularity.Methodology: The research is classified as applied, using a descriptive research method and cross-sectional survey research design. The statistical population of this study includes football fans in Iran. The sampling method in this study was non-probability convenience sampling (200 fans). A four-part questionnaire was used to collect data. Then partial Least Squares Structural Equation Modeling (PLS 3.0) was used for data analysis.Findings: Paying attention to these indicators is of great importance in implementing the model of the impact of online advertising on the intention to purchase football fans. Therefore, based on the study's findings, the model of the effects of online advertising on the intention to buy football fans is confirmed. Based on the results obtained from the combined reliability, extracted variance, model fit coefficient, and goodness-of-fit index in the path analysis, the model is consistent with suitable empirical and theoretical assumptions and has a good fit. Therefore, the model of the impact of online advertising on the intention to purchase football fans is confirmed.Originality: This research evaluated the mediating role of football players' popularity on fans' purchase intention.